Analyzing Students’ Needs in Developing Tourism Reels as Teaching Media of Writing Descriptive Text - Ma'ruf Mahardika, Amar; Ulya, Inayatul (LPPM Universitas Pekalongan, 2025)
This research aims to develop Instagram Reels as an innovative learning media to enhance students' descriptive text writing skills at SMA N 01 Wiradesa. The research design employed in this study was descriptive qualitative, which focuses on analyzing the phenomenon of teaching writing descriptive texts through the use of Instagram tourism reels. The instruments used in this research include documentation, and questionnaires. Data collection was conducted in several stages. First, the questionnaire was distributed to the participants which consisted of students from SMA N 01 Wiradesa. The responses were measured using a Likert scale, which is commonly used to assess attitudes, perceptions, and opinions in a structured format. Documentation involved analyzing teaching modules, learning materials, and student score lists to support the research objectives. Questionnaires consisted of needs analysis. The needs analysis questionnaire identified students' learning requirements. Data analysis employed qualitative methods using descriptive analysis. The needs analysis revealed that 84% of students frequently use Instagram, highlighting its potential as a learning media. The findings indicate that Instagram Reels is highly needed as an effective and engaging learning media to support students in improving their descriptive text writing skills.